Histology of ovine placenta during gestation periods - M. S. Shalal; T. R. Mohammed; A. F. Majeed (Kufa Journal for Veterinary Medical Sciences, 2012)
Placetomes were collected from 93 pregnant slaughtered Ewes  at different  gestation periods , from AL.Falluja slaughter house during the periods from 2, Jully 2009 to 30, December ,2010 . Tissue specimens for microscopic examination were taken from the centers of the sampled placentomes .Immediately following collection ,the samples were fixed in 10% bufferd neutral formalin for 24 h .Tissue specimens were dehydrated in a graded series of alcohol , cleared by xylol and embded in paraffin .Histologic section were cut at 3-4 µm thickness ,Stained with hematoxylin and eosin(H&E) (6).The period of gestation were measured according to Richardson (7) with aquation of x =2.1(Y+17) as x= gestation period in day and Y=the crown Rump